Implementasi Program Parenting untuk Meningkatkan Interaksi Sosial Emosional Orang Tua dan Anak di Desa Naru - Maria Delsiana Sulu Dhera; Konstantinus Dua Dhiu; Andi Nafsia; Elisabeth Tantiana Ngurah (EduInovasi: Journal of Basic Educational Studies, 2026)
This research is motivated by the importance of parents' role in supporting the social and emotional development of early childhood through the implementation of parenting programs. Lack of parental knowledge and skills in parenting results in suboptimal social and emotional development of children, such as the ability to interact, manage emotions, cooperate, and build independence. This study aims to describe the implementation of parenting programs in improving the social and emotional abilities of parents and children in Naru Village. The study used a descriptive qualitative approach with a case study model. Data were collected through interviews, observations, and documentation with parents, early childhood education teachers, and parenting program facilitators. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results show that parenting programs help improve parents' understanding of positive parenting patterns, good communication with children, and the ability to accompany children in managing emotions and social interactions. This research contributes to early childhood education institutions and the community in developing effective parenting programs to support the social and emotional development of early childhood.